Lego mindstorms NXT 2.0 the King's treasure - Floyd Kelly, James. (Apress :, 2009)
Follow the adventures of Evan and his archaeologist uncle as they explore for treasure from an ancient kingdom. Help them succeed by building a series of five robots using LEGO's popular MINDSTORMS NXT 2.0 robotics kit. Without your robots, Evan and his uncle are doomed to failure and in grave danger. Your robots are the key to their success in unlocking the secret of The King's Treasure! In this sequel to the immensely popular book, LEGO MINDSTORMS NXT: The Mayan Adventure, you get both an engaging story and a personal tutorial on robotics programming. You'll learn about the motors and sensors in your NXT 2.0 kit. You'll learn to constructively brainstorm solutions to problems. And you'll follow clear, photo-illustrated instructions that help you build, test, and operate a series of five robots corresponding to the five challenges Evan and his uncle must overcome in their search for lost treasure. Provides an excellent series of parent/child projects Builds creative and problem-solving skills Lays a foundation for success and fun with LEGO MINDSTORMS NXT 2.0 Please note: the print version of this title is black & white; the eBook is full color. Turns and tricks -- MazeRunner—Planning and design -- MazeBot—Build It -- MazeRunner—Program It -- Swing and switch -- RopeSwinger—Design and planning -- RopeSwinger—Build It -- RopeSwinger—Program It -- Hook and pull -- RingTosser—Design and planning -- RingTosser—Build it -- RingTosser—Program It -- Rock and roll -- RampRider—Design and planning -- Ramprider—Build it -- RampRider—Program it -- Grab and release -- ZipLiner—Design and planning -- ZipLiner—Build it -- ZipLiner—Program it -- Treasure and discovery.